Challenges faced by elementary school teachers in the era of educational globalization - Handayani, Fitri; P, Della Hannesti Pratiwi; Sanidra, Anggit; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2026)
Educational globalization is an unavoidable phenomenon in the development of modern education, bringing fundamental changes in the utilization of information and communication technology, the demands of 21st-century competencies, and shifts in students’ values and character. These transformations pose increasingly complex challenges for elementary school teachers, who play a strategic role in shaping students’ foundational knowledge, skills, attitudes, and character. This article aims to provide an integrative examination of the challenges faced by elementary school teachers in responding to educational globalization and to identify potential efforts to address these challenges. The study employs a qualitative descriptive literature review approach by analyzing fifteen national peer-reviewed journal articles published within the last five to seven years. The findings indicate that the challenges faced by elementary school teachers are multidimensional and interconnected, including limited mastery of instructional technology, transformations in pedagogical roles, increasing demands for professional and pedagogical competence, shifts in students’ cultural values and character, and readiness to implement globally oriented curricula. The study further highlights that continuous professional development, supported by institutional and policy-level collaboration, is essential for enabling elementary school teachers to adapt, innovate, and perform effectively in the dynamic context of educational globalization.